1989
DOI: 10.1159/000293620
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Newborn’s Sex in Mixed Maternal-Newborn Lymphocyte Culture Reactivity

Abstract: One-way-stimulated mixed mother-newborn lymphocyte cultures (MMNLC) from male and female newborns were evaluated and compared shortly after delivery. Newborn sex-correlated differences were observed in the strength of the MMNLC reactivity with responding maternal as well as newborn cells. The reactivity of MMNLC with responding maternal cells from male as compared to female newborns was significantly less inhibited in maternal and newborn serum. The inhibitory effect of maternal serum on maternal and male newb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

1989
1989
2005
2005

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 17 publications
1
9
0
Order By: Relevance
“…Komlos et al [12] reported that the blood of mothers with male newborns contains significantly de creased populations of OKT4+ lymphocytes compared to the blood of mothers of female newborns. Likewise, they described an increased reactivity of maternal lymphocytes in mixed mother-newborn lymphocyte culture after deliv eries of male as compared to female newborns [13], and the results were suggested to the correlated to the H-Y male-specific histocompatability antigen [14], If so, the sensitization of the mothers with this antigen in some cases might possibly give a specific IgE reaction, or the alteration of the armature of cell-mediated immunity might indirectly alter the IgE reactions to unrelated anti gens. Studies discriminating between these possibilities would be considerable interest.…”
Section: Discussionmentioning
confidence: 99%
“…Komlos et al [12] reported that the blood of mothers with male newborns contains significantly de creased populations of OKT4+ lymphocytes compared to the blood of mothers of female newborns. Likewise, they described an increased reactivity of maternal lymphocytes in mixed mother-newborn lymphocyte culture after deliv eries of male as compared to female newborns [13], and the results were suggested to the correlated to the H-Y male-specific histocompatability antigen [14], If so, the sensitization of the mothers with this antigen in some cases might possibly give a specific IgE reaction, or the alteration of the armature of cell-mediated immunity might indirectly alter the IgE reactions to unrelated anti gens. Studies discriminating between these possibilities would be considerable interest.…”
Section: Discussionmentioning
confidence: 99%
“…The significantly increased concentration of sialic acid in male as compared to female neonatal lymphocytes observed in this study after 2 and more deliveries suggests the possi bility that sialic acid, by masking specific Ychromosomc-correlated histocompatiblity antigens, may have a contribution in the re duced reactivity observed in MMNLC with male neonatal cells from multi-as compared to primiparae [16], Although the number of primiparae with male neonates was small, the reduced lymphocyte sialic acid level observed for male as compared to female neonates and their mothers suggests the possibility that dose-dependent sialic acid masking of histo compatibility antigens may unspecifically in fluence the immune response [21] and con tribute in some way to an increased reactivity in MMNLC in this specific group of cases [16].…”
Section: Discussionmentioning
confidence: 54%
“…In a previous study [16], a significantly increased immune response was obtained by us in MMNLC after the first delivery with male as compared to female neonatal cells, and this was especially evident in maternal serum. With increasing parity, no such neo nate sex-correlated differences could be ob served in the strength of the MMNLC.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations